Optimalisasi keputusan bisnis melalui analisis SWOT untuk perbankan kompetitif - Firdaus, Violinda Syahgaria (Maliki Interdisciplinary Journal, 2025)
Maintaining competitiveness in the increasingly competitive banking industry is crucial for optimizing business decisions. SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) is an effective way to achieve this. This article discusses how this analysis can be used as a strategic tool to understand a bank's position in facing market challenges and determine the best strategies for company development. Leveraging strengths such as a strong reputation and extensive network can enhance market share and strengthen customer loyalty. Meanwhile, innovation and operational efficiency are necessary to address weaknesses such as high operational costs and limited adoption of new technologies. Opportunities to develop products and services should be capitalized upon, given the growing awareness of Sharia-based goods and government support. Furthermore, flexible and effective risk management strategies are necessary to address external threats such as fintech competition and economic crises. Banks can enhance their competitiveness and sustain their business by incorporating SWOT analysis findings into their decision-making processes. In this study, the SWOT analysis method is crucial for achieving sustainable competitive advantages.